The Effect Of Feeding Combination Of Forage And Different Forms Concentrate On The Performance Of Male New Zaeland White Rabbit - Dughita, Putri Awaliya; Fitroh, Bagus Andika (Bulletin of Applied Animal Research, 2022)
The aim of the research was to study the effect of combination of forage and different forms concentrate on the performance of new zaeland white male rabbit. The material used in this research is 32 new zaeland white male rabbit of 3 month old. The rabbits were distinguished by 4 different treatments that is: Daun Kubis Bunga (DKB) + concentrate of pellet form (T1), Daun Kubis Bunga (DKB) + concentrate of crumble form (T2), Daun Kubis Bunga (DKB) + concentrate of mash form (T3), dan Daun Kubis Bunga (DKB) + concentrate of pasta form (T4). The research method used was experiment using completely random design. The obtained data were analyzed by Anova (Analysis of variance), if there was significant different it would be tested by Duncan's Multipel range test (DMRT). The results of this research showed that he effect of combination of forage and different forms concentrate give a significantly different toward (P<0.01) feed consumption and feed conversion, but give a significantly (P>0,05) on body weight gain. The conclusions of this research was that effect of combination of forage and different forms concentrate give different results to the amount of feed consumption, body weight gain, and feed conversion to new zaeland white male rabbit, even though there are differences on performance but rabbit growth looks normal and in good health condition Keywords: Male rabit, leaf of flower cabbage, different forms of concentrate feed.